Media Framing of Climate Change Action in Carbon Locked-in Developing Countries: Adaptation or Mitigation?. Issue 5 (4th July 2021) - Günay, Defne; İşeri, Emre and Ersoy, Metin and Elega, Adeola Abdulateef
ABSTRACT: As the public draws most of its information on scientific issues from the media, studies of media coverage of climate change have proliferated. Here, we analyze whether newspapers in developing countries frame climate action as an adaptation or mitigation issue. Mitigation refers to activities to reduce or prevent carbon emissions whereas adaptation refers to activities to adjust economic and social systems to the effects of climate change. To this end, we conduct a comparative quantitative analysis of climate change news framing in newspapers from two carbon locked-in developing countries: Nigeria and Turkey. Our first research question is whether newspapers in the two countries frame climate change as a mitigation or adaptation issue. Our second research question is whether there is a relationship between the use of foreign sources and the use of a mitigation frame. We find more adaptation framing in Nigerian newspapers whereas adaptation and mitigation frames are more evenly seen in Turkish newspapers. We also find that the use of foreign sources in news with a climate action frame is negatively correlated with the use of an adaptation frame in our sample. Our findings improve understanding of the factors shaping climate change communication in developing countries.